2022
DOI: 10.1002/cm.21721
|View full text |Cite
|
Sign up to set email alerts
|

An interview with Anthony Brown, Ohio State University, Columbus, OH, USA

Abstract: Formal logic has often been seen as uniquely placed to analyse mathematical argumentation. While formal logic is certainly necessary for a complete understanding of mathematical practice, it is not sufficient. Important aspects of mathematical reasoning closely resemble patterns of reasoning in non-mathematical domains. Hence the tools developed to understand informal reasoning, collectively known as argumentation theory, are also applicable to much mathematical argumentation. This chapter investigates some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Four models were examined: unidimensional (all items load on a single general factor), correlational (three oblique correlated factors), second order (three factors are regressed onto a second order factor), and bifactor (items are simultaneously regressed on their respective three factors and onto a general factor). Models were analyzed considering different fit indices: the Comparative Fit Index (CFI) [ 64 ] and the Non-Normed Fit Index (NNFI) [ 65 ] (values greater than 0.90 show a good fit; [ 64 ]); the Root Mean Square Error of Approximation (RMSEA) and the Standardized Root Mean Square Residual (SRMR) [ 66 ] (values lower than 0.08 show good fit; [ 67 ]). The reliability of the Italian version of the GRAT–RS was analyzed by calculating the Cronbach alphas.…”
Section: Methodsmentioning
confidence: 99%
“…Four models were examined: unidimensional (all items load on a single general factor), correlational (three oblique correlated factors), second order (three factors are regressed onto a second order factor), and bifactor (items are simultaneously regressed on their respective three factors and onto a general factor). Models were analyzed considering different fit indices: the Comparative Fit Index (CFI) [ 64 ] and the Non-Normed Fit Index (NNFI) [ 65 ] (values greater than 0.90 show a good fit; [ 64 ]); the Root Mean Square Error of Approximation (RMSEA) and the Standardized Root Mean Square Residual (SRMR) [ 66 ] (values lower than 0.08 show good fit; [ 67 ]). The reliability of the Italian version of the GRAT–RS was analyzed by calculating the Cronbach alphas.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that testolone has an acceptable safety profile in a recent cancer study [42], and anecdotal evidence suggests increases in lean muscle mass and strength [1] and decreases in fat mass [43]. In a recent study in mice, however, it has been reported that testolone did not significantly increase skeletal muscle but did increase liver injury biomarkers [44]. This same study mentioned the possibility that RAD140 may act as an agonist for the AR outside of the muscles since RAD 140 supplementation decreased the effects of testosterone on the prostate and seminal vesicles [44].…”
Section: Testolonementioning
confidence: 99%
“…Stigmatised individuals must continually choose what to disclose and what to conceal about their participation in BDSM (Meeker, 2013). Fear of discovery may mean that practitioners become secretive, have pseudonyms and live double lives which can lead to stress, reduced quality of life, dissatisfaction and disengagement from aspects of mainstream society (Brown, 2010;Moser, 1999).…”
Section: Stigma Management and Effects Of Stigmatisationmentioning
confidence: 99%